Pengembangan E-Modul Matematika Interaktif Terintegrasi Kahoot! untuk Mendukung Literasi Matematis Siswa SMP - Tamur, Maximus; Pantaleon, Kristianus Viktor (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
In the literature, it is confirmed that there is a strong correlation between technological literacy and students' mathematical literacy levels and that technological literacy influences individual mathematical literacy. The integration of digital games can reduce the decline in student interest due to changes in the learning system, which are thought to support mathematical abilities. Unfortunately, there are not many mathematics teaching materials that specifically integrate technology in promoting mathematical literacy skills. In this regard, this research aims to develop an interactive mathematics e-module that integrates Kahoot! as a learning medium. By using questionnaire, observation and documentation techniques in the form of validation sheets, photo and video documentation, observation sheets and questionnaire sheets, this development research produces a product in the form of an interactive math e-Module integrated with games using the Kahoot! Platform. From the results of development using the Borg & Gall model, it was concluded that the product developed was declared valid and suitable for use in the learning process and was useful and helped students learn both in class and independently outside of class.